1968
DOI: 10.1038/bjc.1968.47
|View full text |Cite
|
Sign up to set email alerts
|

Possible host resistance in carcinoma of the breast: a histological study

Abstract: Images Figs. 6-8 Figs. 9-11 Figs. 1-3 Figs. 4-5 Fig. 13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
7

Year Published

1969
1969
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(91 citation statements)
references
References 12 publications
5
79
0
7
Order By: Relevance
“…]DISCUSSION Evidence has accumulated from a number of studies in man, showing that regional tumour lymph nodes, draining a variety of solid tumours of different pathological types, show an alteration of their micro-architecture (Black et al, 1953;Hamlin, 1968;Tsakraklides et al, 1973;Patt et al, 1975). The results of this present investigation of axillary lymph nodes draining mammary carcinoma confirms these findings.…”
Section: Tumour Histologysupporting
confidence: 81%
See 2 more Smart Citations
“…]DISCUSSION Evidence has accumulated from a number of studies in man, showing that regional tumour lymph nodes, draining a variety of solid tumours of different pathological types, show an alteration of their micro-architecture (Black et al, 1953;Hamlin, 1968;Tsakraklides et al, 1973;Patt et al, 1975). The results of this present investigation of axillary lymph nodes draining mammary carcinoma confirms these findings.…”
Section: Tumour Histologysupporting
confidence: 81%
“…Black et al, 1953;Hamlin, 1968;Tsakraklides et al, 1973;Patt et al, 1975). This altered cellular organisation has been associated in a number of studies with a diminished incidence of tumour spread to the regional lymph nodes (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antigens associated with transformation to the malignant state may be expressed (Laurence and Neville, 1972) and choriocarcinoma is neither more nor less likely than other tumours to have such antigens. It is interesting that similar cellular infiltrates to those seen in choriocarcinoma have also been described in other tumours, for example, in carcinoma of the stomach (Black, Opler and Speer, 1954), carcinoma of the breast (Berg, 1962;Black, Opler and Speer, 1956;Hamlin, 1968), malignant melanoma (Cochran, 1969) and neuroblastoma (Lauder and Aherne, 1972). Thirdly, since choriocarcinoma is a malignant allograft (Dowling, 1957;Hirsch, 1962) it may also exhibit individual-specific or transplantation antigens, inherited from the male parent of the antecedent conception.…”
Section: Discussionmentioning
confidence: 72%
“…This tissue cellular response may represent the morphological features of a host defence mechanism similar to that seen in other human tumours such as breast cancer (Hamlin, 1968;Bloom, Richardson and Field, 1970), neuroblastoma (Martin and Beckwith, 1968), seminoma (Dayan, 1966), and stomach cancer (Black, Opler and Speer, 1956). Levy, Mahaley and Day (1972) have reported that patients with glioblastomata and other intracranial neoplasms possessed peripheral blood lymphocytes which were specifically cytotoxic to cultured autologous tumour cells in vitro.…”
Section: Resultsmentioning
confidence: 83%